The coming central bank digital currency revolution and the e-CNY - WANG, Heng (Institutional Knowledge at Singapore Management University, 2023)
The only central bank money individuals and businesses have today is cash. Everything else they use as money is commercial bank promises. Central bank digital currencies (“CBDC”) will likely change all this by putting central bank money into everyone’s hands. China is a front runner in this revolution, and its CBDC, the e-CNY, may well in time profoundly affect the international economic order. This article analyses the major considerations around the e-CNY, its ramifications, in particular for trade, and its possible challenges.